Modified V-Y Fasciocutaneous Flap Reconstruction After Abdominoperineal Resection in Irradiated Patients Prevents Wound Dehiscence and Associated Complications: A Retrospective Analysis and Benchtop Confirmation. Issue 2 (February 2019) - Kokosis, George; Phillips, Brett T.; Soo, Joanne; Poveromo, Luke; Erdmann, Detlev; Mantyh, Christopher R.; Migaly, John; Levinson, Howard
Abstract : Background: Primary perineal closure following abdominal perineal resection (APR) is reported to have a wound complication rate as high as 66%, whereas flap reconstruction reduces wound complications to 15% to 35%. A modified de-epithelialized V-Y fasciocutaneous flap aims to further improve results in this patient population. Methods: To study the breaking force of a simple interrupted suture in either skin or subcutaneous fat, various quantitative assessments were performed in a porcine flap model using uniaxial static tensile testing with an Instron tensiometer, with a single or triple row of 3 Vicryl sutures in both skin and fat. An outcomes analysis was performed in 24 patients who underwent modified V-Y flap reconstruction after APR. Primary outcome was wound complications including infection, dehiscence, seroma, hematoma, and pelvic fluid collections. Results: Tensile strength of sutures anchored in skin was found to be up to 8 times stronger than sutures anchored in subcutaneous fat in a single row and 3 times as strong in 3 rows (breaking force, 500.2 N vs 263.7 N). In our patient cohort of 24 irradiated cancer patients, 10 (42%) had wound healing complications. Wound dehiscence of various degrees accounted for 80% of these complications. Five patients with wound complications (50%) had associated pelvic fluid collections (infection, 1; wound dehiscence, 4). Minor dehiscence was more likely to occur after suture removal and less likely to be associated with pelvic collections compared to patients with major dehiscence. Our study yields total complication rates lower than what is reported in the literature for anterolateral thigh or gracilis flap including much lower infection rates, and almost similar results to the commonly used vertical rectus myocutaneous muscle. Conclusion: Tension-free de-epithelialized V-Y flap use after APR effectively reconstructs the defect while eliminating an additional donor site. Benchtop studies suggest enhanced flap integrity yielded by layered closure. Wound complications can be managed with local care in their majority (90%). Staggering or delaying suture removal can decrease minor dehiscence. Based on analysis of our results, review of the literature and consideration of donor site morbidity, we believe that modified V-Y flap is the best approach for APR reconstruction in irradiated patients.